Trade Liberalisation and Factor Mobility: An Overview. - Venables, A (Centre for Economic Performance, LSE, 1997)
This paper analyses the ways in which liberalisation of goods trade may change factor prices and the incentives for factor mobility. While trade liberalisation reduces the incentives for factor mobility in a Heckscher-Ohlin model, it may increase it in a specific factors model (in which there is a richer range of substitution/complementarity relationships between factors of production) and in models in which there are increasing returns to scale.